Perceptions of youths towards traditional and modern approaches to parenting in Malaysia - Yong, Shan Ting (2023)
Parents are the person who the child first comes into contact with when born. They play an important role in children’s development in which the growing environment formed by parents, the attitude and behaviors of parents will influence children. Parents will be the first person they meet and family is the first place where they grow up. Parenting becomes more important as children are strong learners. Thus, this research aims to study traditional and modern parenting from youths’ perspectives, and to study the most common parenting style used in Malaysia nowadays. The study used quantitative research methods while answering the Google survey form to collect the data from 120 Malaysian youths who are 18-25 years old. All the data will be analyzed by using Microsoft Excel and shown in tables. The findings of this research shows that there is a positive relationship between the RO Besides, the result also shows that the labels and terms which represent traditional parenting style and modern parenting style are also changing as time passes. Therefore, this research concluded that the characteristics of parenting style youths receive, they are more likely to apply in the future also, and parenting styles may continue to change through the generations.